Group Work Training For Counselors: A Syllabus. - Davy Vera, Jorge (Encuentro Educacional)
This article describes a syllabus for an introductory group work class at Master and Doctorate levels in Counseling and related professional fields. lt is based upon current trends in the area of training for group work specialists, trends that are represented by the Association for Group Work Specialist (ASGW). The syllabus contains: (1) A personal phylosophy of group work training, where the author assumes a position about what group work means. (2) A Course description, which included the goals and objectives and the lnstructional and the didactic strategies, and other support resources. (3) Format of class meetings that explains what assignments and activities are u sed in fomenting the learning experience. (4) Appendix 1, which describes The Curve-shaped Model that supported the syllabus design and the class schedule.